Interfaith Dialogue in the Twentieth Century: A Study of the Contribution of Bediuzzaman Said Nursi and Seyyed Hossein Nasr - Firdous, Qudsia; Sabiha, Taimia; Yasin, Zahid (Journal of Islamic and Religious Studies, 2020)
Interfaith dialogue has been initiated in the nineteenth century as an ecumenical discourse that was transformed and adapted by almost all religions as a means of building interfaith harmony. However, in the case of Islam Muslim scholars had to respond in a variant geopolitical panorama of the post-colonial world, struggling to place themselves between strong notions of Liberté, Egalité, Fraternité and safeguarding the traditional fabric of Islam. The present paper expounds on the approaches of two Muslim scholars in the twentieth century are Bediuzzaman Said Nursi (1876-1960), an eminent Turkish spiritual leader, and Seyyed Hossein Nasr (1933-), an Iranian origin, contemporary Muslim philosopher in the United States. Both of them are well-known for their contribution to interfaith dialogue with their unique methodologies. The main research question is; to study the contribution of Nursi and Nasr in the field of interfaith dialogue which is presumably led by Protestants as well as Catholics. The methodology includes comparative and historical analysis which has been applied to explore the academic as well as the social contribution of both the scholars focusing on their enterprise of interfaith dialogue in a pluralistic society. The article ends up concluding that both Nursi and Nasr agreed on the importance of dialogue for a co-existing means while differed in their methods to initiate it.